Antimicrobial resistance in zoonotic bacteria in Bangladesh: a converging crisis at the human–animal–environment interface (Asian Journal of Medical and Biological Research, 2026)
Abstract not availableAsian J. Med. Biol. Res. 2026, 12(1), 1-4